ANALISIS PENDAPATAN DAN RISIKO USAHATANI KUBIS PADA LAHAN KERING DAN LAHAN SAWAH TADAH HUJAN DI KECAMATAN GISTING KABUPATEN TANGGAMUS - Huda Nur Aini; Fembriarti Erry Prasmatiwi; Wuryaningsih Dwi Sayekti (Lampung University, 2015)
The research aims to assess: the comparative productivity and income of cabbage on dried land and rainfed field, the level of risk of cabbage farming on dried land and rainfed field, the behavior of farmers against the risk of cabbage faming on dried land and rainfed field, and the impact of incomes, risks and the other factors on the behavior of farmers against the risk of cabbage farming on dried land and rainfed field. This research was conducted in two villages, namely Campang Village and Gisting Atas Village of Gisting Sub district of Tanggamus Regency. The first goal was analyzed using different test of productivity and income. The second goal was analyzed by different test of coefficient variation. The third goal using Bernoulli and Neumann Morgenstern Techniques, and the fourth goal was analyzed by binary logit regression. The finding showed that productivity and income of cabbage farm in rainfed field was greater than productivity and income on dried land. Risk of cabbage on dried land farming was greater than rainfed field, 93.18 percent of farmers in dried land were neutral in their behavior and 6.82 percent of farmers were not brave enough to take risks; whereas the farmers in the rainfed field were 41.94 percent neutral and 58.06 percent of farmers were reluctant to take risk. Moreover, there was no farmers behave dare to risk on dried land and in the rainfed field). The factors that influence farmers' behavior towards risk of cabbage farming on dried land and rainfed field were farm income, land area, age of the farmer, the number of dependents, and the type of land. Key words: behavior of farmer, income, productivity, risk